2019
DOI: 10.1111/pops.12588
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Backlash Against Immigration From Richer Countries? International Hierarchy and the Limits of Group Threat

Abstract: Why do immigrants from particular countries systematically face more opposition? To resolve inconsistencies of prevailing group‐threat theories, I reintroduce a long‐standing hypothesis stipulating that people have a disposition for maintaining status hierarchy between ethnic groups. Accordingly, independent of perceived economic or cultural threat, natives are more likely to prefer immigrant groups of higher status based on the development level of the group's national origin. To test this argument, I exploit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 71 publications
1
12
0
Order By: Relevance
“…This division can further complement a prominent—but often less analytically useful—juxtaposition of economic and cultural behavioral causes. For instance, the current debate about the rise of populism that mostly focuses on economic anxiety and cultural backlash as exhaustive explanations (e.g., Norris & Inglehart, 2019) may be missing an important preference variation in the electorate (also see Kustov, 2019b, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…This division can further complement a prominent—but often less analytically useful—juxtaposition of economic and cultural behavioral causes. For instance, the current debate about the rise of populism that mostly focuses on economic anxiety and cultural backlash as exhaustive explanations (e.g., Norris & Inglehart, 2019) may be missing an important preference variation in the electorate (also see Kustov, 2019b, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…An alternative and perhaps more universal explanation relates to the place in the ethnic hierarchy occupied by target out-groups. Previous research demonstrated that while people show an inclination to maintain status hierarchy between groups, natives prefer immigrant groups of higher status to those of lower status (Kustov 2019). Bessudnov (2016), in his study on public attitudes toward immigrants, concluded that the effect of immigrant concentration (which may be perceived as a measure of the relative size of an out-group) on attitudes toward immigrants appears to be stronger for groups positioned lower in the ethnic hierarchy.…”
Section: Discussionmentioning
confidence: 99%
“…In specifically analyzing periodic changes in the host societies' immigrant populations, this study furthermore contributes to the growing literature investigating whether different types of immigrants are perceived as more or less threatening (Bloom et al, 2015a(Bloom et al, , 2015bSemyonov, 2016, 2019;Kustov, 2019;Stephan et al, 2005). To date, it remains unclear how far increasing intra-European migration (mostly from East to West) affects Western European attitudes toward immigrants compared with immigration from the Global South.…”
Section: Introductionmentioning
confidence: 94%
“…Second, with regard to immigration from outside Europe, a further distinction of immigrant origin needs to be drawn. Independent of their actual economic and cultural characteristics, immigrants from less developed countries face greater rejection (Kustov, 2019). By definition, this implies immigrants from the Global South, who on average hold a lower socioeconomic status than European citizens.…”
Section: The Role Of Immigrant Originmentioning
confidence: 99%
See 1 more Smart Citation